Curcumin Promotes the Recovery of Motor Function After Brachial Plexus Avulsion Injury in Rats - Sijing Li; Bing He; Guijuan Zhou; Lin Wu; Xuanwei Wen; Limin Deng; Shudong Lin; Guozhi Liu; Shuangxi Chen; Zijian Xiao (Brain and Behavior)
ABSTRACT Background and Purpose Brachial plexus root avulsion (BPRA) often results in the loss of upper limb motor function. Curcumin (CUR) has been proven to have neuroprotective properties in various neurological disorders due to the effects of anti‐oxidative stress and anti‐inflammation. Therefore, in this study, we focused on the effect of CUR on the recovery of motor functions in rats after BPRA. Methods Adult male Sprague‐Dawley rats were used to build the BPRA and reimplantation model and randomly divided into two groups: the NS group (treated with saline) and the CUR group (treated with 40 mg/ml CUR), with 10 rats in each group. After conducting the Terzis grooming test (TGT) to assess the recovery of motor function, the anterior horn of the spinal cord was collected for detecting the inflammatory responses using Western blot, the musculocutaneous nerves were collected for detecting the motor neuron survival and myelination using Luxol fast blue (LFB) staining or real‐time quantitative PCR (qRT‐PCR), and the biceps brachii were collected for detecting muscle atrophy using hematoxylin and eosin (H&E) staining. Results CUR can significantly enhance the motor recovery in rats following BPRA, reduce inflammation in the anterior horn of the spinal cord, improve the motor neuronal survival and axonal remyelination in musculocutaneous nerves, alleviate muscle atrophy. Conclusion CUR promotes the recovery of motor function in rats after BPRA by inhibiting inflammation, reducing motor neuron death, promoting axonal remyelination, and reducing muscle atrophy, thus laying a foundation for the treatment of BPRA with CUR.